030 Multi-centre study of the emergency management of allergic reactions and anaphylaxis. (14th September 2011) - Helin, H; Perkin, M; Gumm, R
Abstract : Objectives and Background: The Royal College of Paediatrics and Child Health (RCPCH) recently published its care pathway for anaphylaxis incorporating an algorithm with the stages of ideal care and a set of competences required to diagnose, treat and optimally manage anaphylaxis. In order to assess current practice we investigated the quality of documented assessment and treatment of paediatric allergies in Accident and Emergency (A&E). Methods: Retrospective case review of children presenting with allergic reactions to A&E at two large teaching hospitals during 1 year. Results: Total number of cases included was 187 (96 hospital A, 15% severe, 91 hospital B, 12% severe). Urticaria, angiooedema and pruritus were the main presenting symptoms. Enquiry of previous allergies was not recorded in 31%/38% (A/B) of cases. Recording of ABCD assessment of all and the most severe reactions (systemic symptoms) varied between hospitals (Abstract 030 table 1). Types of medications used were similar with antihistamines (55%/67% A/B), steroids (26%/38% A/B) and bronchodilators (4% both) being the main treatments. Number of admissions (to paediatric assessment unit and wards) differed 16%/5% (A/B). Both hospitals had low recorded referral rates to allergy clinic (8%/11% A/B) and allergen avoidance advice (8%/12% A/B). Medication on discharge was given to 29%/59% (A/B), mainly antihistamines. Conclusion: The RCPCH care pathway sets best practice. While we reviewed written notes which may not fully reflect actual consultations, current practice would appear to be falling significantly short of the ideal care proposed.